Teaching Engagement and Preschool Practitioners’ Disciplining Practice in Post-Corporal Punishment Era: A Correlational Quantitative Evaluation - O. Okeke, Chinedu I.; S. Ugwuanyi, Christian; C. Okeke, Charity; C. Ugwu, Gloria; N. Ngwoke, Anthonia; O. Ifelunni, Clara; N. Aye, Eucharia; T. Nnamdi, Ekeanyanwu (International Journal of Psychosocial Rehabilitation, 2024)
Studies have been conducted on the disciplining practices adopted by preschool teachers at the post-corporal punishment era. However, there is dearth of empirical evidence on the nature of the relationship between the preschool teachers’ disciplining practice and their teaching engagement. Thus, the researchers explored the relationship between preschool teachers’ disciplining practice and their teaching engagement using school type as a possible moderator. A correlational survey research design was adopted for the research using a sample of 156 preschool teachers. Teacher disciplining practice and teaching engagement questionnaires were used for data gathering. These instruments were face validated and trial tested yielding internal consistency reliability indices of 0.79 and 0.82 respectively using the Cronbach alpha method.Linear regression analysis was conducted to answer the research questions and test the corresponding null hypotheses at 5% probability levels.The results of the analysis showed that preschool teachers’ disciplining practice had as significant (p< .05) positive relationship with teaching engagement. It was also revealed that school type had significant (p< .05) moderating influence on the relationship between preschool teachers’ disciplining practice and teaching engagement.This implies that when preschool teachers adopt better classroom disciplining practice, they will have good and effective teaching engagement.